1997
DOI: 10.1111/j.1349-7006.1997.tb00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Rat Hepatocarcinogenesis by Dimethylarsinic Acid: Association with Elevated Ornithine Decarboxylase Activity and Formation of 8‐Hydroxydeoxyguanosine in the Liver

Abstract: Arsenicals are epidemiologicaUy significant chemicals in relation to induction of liver cancer in man. In the present study, we investigated the dose‐dependent promotion potential of dimethylarsinic acid (DMAA), a major metabolite of inorganic arsenicals in mammals, in a rat liver carcinogenesis model. In experiment 1, glutathione‐S‐transferase placental form (GST‐P)‐positive foci, putative preneoplas‐tic lesions, were employed as endpoints of a liver medium‐term bioassay for carcinogens (Ito test). Starting 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Previous studies have reported an increase in levels of 8-OHdG in urine samples from mice gavaged with 720 mg/kg of DMA (Yamanaka et al, 2001). In a long-term study of carcinogenesis in rats, hepatic 8-OHdG levels were increased in DMA-treated rats, suggesting an increased effect of ROS on DNA (Wanibuchi et al, 1997).…”
Section: Introductionmentioning
confidence: 86%
“…Previous studies have reported an increase in levels of 8-OHdG in urine samples from mice gavaged with 720 mg/kg of DMA (Yamanaka et al, 2001). In a long-term study of carcinogenesis in rats, hepatic 8-OHdG levels were increased in DMA-treated rats, suggesting an increased effect of ROS on DNA (Wanibuchi et al, 1997).…”
Section: Introductionmentioning
confidence: 86%
“…DMeAs, a metabolite of iAs, induced DNA damage via formation of ·O 2 -and dimethylarsenic peroxyl radical (39,40). 8-Hydroxy-2´-deoxyguanosine (8-OhdG), one of the major ROS-induced DNA basemodified products, was detected in the skin of patients with arsenic-related Bowen's disease (41) and in the liver of rats administered DMeAs (42). Our recent data (43) from animal experiments revealed that ·O 2 -, which was identified as a Tiron-reactive signal (Dojindo Lab., Kumamoto, Japan), was generated in intact aortic rings from rabbits chronically exposed to 5 mg/L of arsenate in drinking water for 18 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Directly or indirectly, arsenic-induced oxidative stress can induce further damages in cells, and these oxidative injuries are reported to associate with arsenical carcinogenesis. Both in mouse and human skins, arsenic can induce oxidative damage in cellular DNA and generate 8-hydroxyl-2¢-deoxylguanosine (8-OHdG) oxidative DNA adducts [24][25][26]. Clinical studies in arsenic-induced Bowen's disease (As-BD) indicate that the increased 8-OHdG levels are positively correlated to the lesional arsenic concentration [26], suggesting the involvement of oxidative stress in arsenical skin carcinogenesis.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%